Immigrants’ use of primary health care services for mental health problems - Straiton, Melanie (BioMed Central, 2014)
BACKGROUND: Equity in health care across all social groups is a major goal in health care policy. Immigrants may experience more mental health problems than natives, but we do not know the extent to which they seek help from primary health care services. This study aimed to determine a) the rate immigrants use primary health care services for mental health problems compared with Norwegians and b) the association between length of stay, reason for immigration and service use among immigrants. METHODS: National register data covering all residents in Norway and all consultations with primary health care services were used. We conducted logistic regression analyses to compare Norwegians’ with Polish, Swedish, German, Pakistani and Iraqi immigrants’ odds of having had a consultation for a mental health problem (P-consultation). RESULTS: After accounting for background variables, all immigrants groups, except Iraqi men had lower odds of a P-consultation than their Norwegian counterparts. A shorter length of stay was associated with lower odds of a P-consultation. CONCLUSIONS: Service use varies by country of origin and patterns are different for men and women. There was some evidence of a possible ‘healthy migrant worker’ effect among the European groups. Together with previous research, our findings however, suggest that Iraqi women and Pakistanis in particular, may experience barriers in accessing care for mental health problems.